195k views
0 votes
A.) If log(2x + 3) -log(x - 1) = 3, then the equation in exponential form is 10^3= (2x + 3)(x - 1).

Is this true or false? If false how do I fix it

User Hynekcer
by
4.3k points

1 Answer

4 votes

Explanation:

One of the logarithm rules states the following:


log{a} - log{b} = log{(a)/(b)}

For this problem, that means the following:


log{2x + 3} - log{x - 1} = log{(2x + 3)/(x - 1)}

So now we have the following:


log{(2x + 3)/(x - 1)} = 3

Rolling the log, we get the following:


10^(3) = (2x + 3)/(x - 1)

User Dharmang
by
5.8k points